2021
DOI: 10.1080/23311975.2021.1935084
|View full text |Cite
|
Sign up to set email alerts
|

Who buys organic food? Understanding different types of consumers

Abstract: Globally, concerns regarding consumers' food quality and safety have increased. There is an increase in the search of alternative healthy and safe food that also enhances immunity. Organic food eliminates most of the concerns that consumers have. Market experts expect the Indian domestic organic food market to grow rapidly in the coming years. This study aims to understand the characteristics, attitudes, and buying patterns of different types of consumers so that producers, sellers, and the government can desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 48 publications
0
6
0
1
Order By: Relevance
“…The results of our own research in relation to gender are shown in Figure 1 . Taking into account the factor of age, it has been shown that younger consumers are more aware of organic food, prompting them to buy it more often [ 58 , 60 ]. For young people, a lifestyle based on organic food provides a sense of mental stability in life, a life lived in harmony with nature, history and their perception of health.…”
Section: Resultsmentioning
confidence: 99%
“…The results of our own research in relation to gender are shown in Figure 1 . Taking into account the factor of age, it has been shown that younger consumers are more aware of organic food, prompting them to buy it more often [ 58 , 60 ]. For young people, a lifestyle based on organic food provides a sense of mental stability in life, a life lived in harmony with nature, history and their perception of health.…”
Section: Resultsmentioning
confidence: 99%
“…They expect that modern food system must deliver food that is risk-free and safe. Therefore regarding food safety, people trust certification symbols and labels (Gumber & Rana, 2021). People who care about the environment and animal welfare have more positive attitudes of organic food (Honkanes et al 2006).…”
Section: Reasons For the Shift In Consumer's Attitude Towards Organic...mentioning
confidence: 99%
“…Consumer prefers organic food not just due to its health and ecology concerns but also because consumer like the way it tastes. They are willing to pay more for it because of the flavor's authenticity (Hill & lychehann, 2002;Gumber & Rana, 2021).…”
Section: Reasons For the Shift In Consumer's Attitude Towards Organic...mentioning
confidence: 99%
“…Vigar et al (2020) in a systematic review reports that despite significant positive outcomes in longitudinal studies, increased organic intake was associated with reduced incidence of infertility, birth defects, allergic sensitization, otitis media, preeclampsia, metabolic syndrome, high BMI, and non-Hodgkin lymphoma. Organic food is also achieving popularity as an immunity booster food (Gumber et al, 2021). However, the nonregulated and specifically the purchase of non-certified organic food is still an unexplored avenue in this regard, that either non-certified organic food is equally considered safe food or there are other factors that contribute towards its purchase.…”
Section: Literature Reviewmentioning
confidence: 99%